Vitamin D in tuberous sclerosis complex-associated tumors - Nobutoki, Tatsuro (Frontiers in Pediatrics, 2024)
Mammalian target of rapamycin inhibitors (mTORi) have been used to treat pediatric tuberous sclerosis complex (TSC)-associated tumors, particularly in cases with contraindications to surgery or difficulties in complete tumor resection. However, some patients experience side effects and tumor regression after discontinuation of the treatment. Therefore, there is an urgent need to develop drugs that can be used in combination with mTORi to increase their efficacy and minimize their side effects. 1,25-Dihydroxyvitamin D3 (1,25-D), which has anticancer properties, may be a promising candidate for adjuvant or alternative therapy because TSC and cancer cells share common mechanisms, including angiogenesis, cell growth, and proliferation. Vitamin D receptor-mediated signaling can be epigenetically modified and plays an important role in susceptibility to 1,25-D. Therefore, vitamin D signaling may be a promising drug target, and in vitro studies are required to evaluate the efficacy of 1,25-D in TSC-associated tumors, brain development, and core symptoms of psychiatric disorders.